ETHNIC TITLES IN THE 5TH – 6TH CENTURIES AH (11TH – 12TH CE) IN THE BOOK SIYAR A’LAM AL- NUBALA (BIOGRAPHIES OF NOBLE FIGURES) BY AL- DAHABI (D. 748AH/ 1347CE). - Khalil, Mehvan; Yusuf, Falah (Humanities Journal of University of Zakho, 2025)
There is no doubt that the period of the (5th – 6th AH /11th – 12th AD) in the history of the Islamic state is considered a period full of important events and changes. In these two centuries, rapid and diverse transformations took place. Civil aspects were not deprived of these changes, the use of titles is an ancient phenomenon present among all peoples, and all of these peoples use titles according to their circumstances, customs, and traditions. After the advent of Islam, a new type of change arose in the use of titles, especially their circumstances, customs, and traditions, especially since this religion gave great importance to all aspects of life and beautiful dealings with each other. Islam also emphasized avoiding the use of bad titles, and the Islamic reigion permits the use of titles that do not lead to disrespect and contempt for people. During the Abbasid era, the use of titles increased for various purposes, among these diverse titles were ethnic titles, which was considered an important title. In general ethnic titles are divided into three main types. These three types of titles will be discussed, with examples of each type into the three types of ethnic titles. The impact of the use of these titles on famous figures will also be shown.